The dynamics and frontiers of video game social research in communication studies-a scientometrics analysis based on CiteSpace and VOSviewer - Zhao, Fan; Alsagoff, Syed Agil; Abdullah, Karmilah; Wu, Xuanyi (Redfame Publishing, 2023)
In this media-rich era, digital entertainment in the form of video games has a major impact on our social interaction and productivity in a borderless social mode. As a result, in order to comprehend the research progress of video game, CiteSpace and VOSviewer were used for scientometrics and knowledge mapping in this study. It displays the state of development, fundamental structure, and frontier areas of video game social communication. The mapping is based on 448 publications collected through Web of Science core database searches. The findings indicate that (1) video game social research has gained increasing attention over the last 23 years, with a curvilinear growth in annual publications, but a core authorship group has yet to materialize, and the United States institutions dominate the number of publications on this topic. (2) Gaming behaviors, gender studies, media effects, and gaming experiences have emerged as the four main hotspots of research in this field under the keyword co-occurrence and clustering analyses. (3) Research in this area has traditionally concentrated on violent, addictive, and other problematic gaming behaviors. The findings of this study forecast future trends in the study of video game social communication and provide the groundwork for more in-depth research.